IMPLEMENTATION OF THE MODELING METHOD ON THE SUBJECT OF ISLAMIC RELIGIOUS EDUCATION ASPECTSAL-QUR'AN AND WORSHIP IN RANCAKALONG PUBLIC HIGH SCHOOL - Suherman (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2024)
One of the problems faced by the world of education is the weak learning process. Students in the learning process are less encouraged to do activities and practice learning materials. The learning process in the classroom is directed towards students' ability to memorize information, so that aspects of skills and attitudes are neglected. This condition also occurs in Islamic religious education lessons. As a result, when students graduate from school, they are theoretically smart but poor in application. This study aims to describe the implementation of learning methods that encourage students to think and apply the material obtained at school in everyday life. The method in question is the modeling method. Through the modeling method, students learn by imitating a model displayed in front of the class. The model can be a teacher, student or other person who is worthy of imitation. The problems revealed from this research are 1) To what extent is the planning of PAI learning through modeling method, 2) To what extent is the implementation of the modeling method in PAI subjects, 3) To what extent is the evaluation of PAI learning through the modeling method. This research took place in SMA Negeri Rancakalong, Sumedang Regency. The research data were obtained through observation, interview and documentation techniques. Data analysis was conducted through qualitative data analysis which aims to describe and interpret the data in the form of words not numbers. The results showed that through good lesson planning will make it easier for teachers to carry out learning. Learning planning is not limited to making learning administration but teachers prepare physically, material, attitude and appearance when going to carry out learning. The implementation of learning through the modeling method is proven to make it easier for students to understand learning materials because students practice directly through imitating models made by teachers, students, and even other people. Through the modeling method, abstract learning materials become more concrete and reduce verbalism. The fact of this research reminds teachers that models are necessary in teaching students and what is used as a model by itself must be something that is right and worthy of imitation. Through the modeling method students become active and creative in learning and encourage them to actualize themselves.